Practical Experience with Distance Measurement Based on Single Visual Camera (Advances in Military Technology, 2022)
The paper deals with the problem of distance measurement of stationary target by single visual camera in laboratory conditions. The paper describes the practical experiments performed in order to estimate the distance of a target using visual odometry. For the estimation of the distances, we used a camera and a target. For these estimations, photos were taken to obtain the coordinates of reference points on the target surface. The coordinates obtained were used in optical equations to estimate distances of the target in the space. The paper explains the procedures made for the experiment preparation, describes the experiments and finally analyses the results acquired. These practical experiments establish a basis for the implementation of the position algorithm into navigation subsystem of swarm robots.
Keywords: single visual camera; distance measurement; error analysis; image analysis; optical properties